Ocular Rosacea: an updated review - Mohamed Noriega, Karim; Loya Garcia, Denise; Vera Duarte, Guillermo Raul; Morales Wong, Fernando; Ortiz Morales, Gustavo; Navas, Alejandro; Graue Hernández, Enrique O.; Ramirez Miranda, Arturo (Wolters Kluwer Health, 2025)
Purpose: Ocular rosacea is a chronic inflammatory disorder affecting the ocular surface, often associated with cutaneous rosacea. This review aims to explore its pathogenesis, treatment approaches, and future directions for management. Methods: A review of current literature on the pathophysiology, clinical features, and treatment strategies of ocular rosacea in adults and children (pediatric blepharokeratoconjunctivitis) was conducted. Emerging research on immune dysregulation, microbiome alterations, and potential therapeutic targets was analyzed. Results: Ocular rosacea involves dysregulation of the immune and neurovascular systems, with toll-like receptor activation and complement system involvement leading to chronic ocular surface inflammation. Alterations in the ocular microbiome have been implicated in disease progression. Treatment strategies emphasize a stepwise approach, incorporating ocular and skin hygiene, lifestyle modifications, and pharmacological interventions. Recent advancements in understanding the disease mechanisms have led to the exploration of targeted therapies, including biologics and small molecule inhibitors. Conclusions: Ocular rosacea remains challenging to diagnose and treat, particularly in children (pediatric blepharokeratoconjunctivitis), often leading to delayed intervention and poor outcomes. A multidisciplinary approach, including new therapeutic options, holds promise for improving patient care. Further research into the genetic and molecular basis of ocular rosacea may enable more personalized treatments.